Malignant progression of laryngeal papilloma associated with human papilloma virus type 6 (HPV-6) DNA. Issue 3 (March 1988) - Zarod, A P; Rutherford, J D; Corbitt, G
Abstract : A case of laryngeal squamous papilloma in the early stages of development showed histological features suggestive of virus infection. Five years later positive evidence of HPV-6 infection was obtained at a time when the lesion had developed into a squamous cell carcinoma. It is concluded that this case represents a complete example of the virus to papilloma to carcinoma sequence, and as far as is known, is the first reported case of its kind in the larynx.